2008
DOI: 10.1175/2007jas2546.1
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Parameterization of Heterogeneous Ice Nucleation for Multiple Chemical Species of Aerosol

Abstract: A novel, flexible framework is proposed for parameterizing the heterogeneous nucleation of ice within clouds. It has empirically derived dependencies on the chemistry and surface area of multiple species of ice nucleus (IN) aerosols. Effects from variability in mean size, spectral width, and mass loading of aerosols are represented via their influences on surface area. The parameterization is intended for application in largescale atmospheric and cloud models that can predict 1) the supersaturation of water va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
532
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(558 citation statements)
references
References 123 publications
21
532
5
Order By: Relevance
“…This approach captures most of the features and details desired for predicting ice nucleation in cloud and climate models, absent explicit treatment of different ice nucleation mechanisms. A number of input parameters are required, and specialized observational data are needed for the evaluation of the various scaling factors used in the parameterization; the factors presently are based on data from just two field studies (31). The validity of this approach has been demonstrated in selected cases, but remains to be validated for the array of aerosol compositional and cloud scenarios in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach captures most of the features and details desired for predicting ice nucleation in cloud and climate models, absent explicit treatment of different ice nucleation mechanisms. A number of input parameters are required, and specialized observational data are needed for the evaluation of the various scaling factors used in the parameterization; the factors presently are based on data from just two field studies (31). The validity of this approach has been demonstrated in selected cases, but remains to be validated for the array of aerosol compositional and cloud scenarios in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…It may be some time before the establishment of an adequate particle-by-particle database linking ice nuclei activation properties (i.e., dependence on thermodynamics) to physical and chemical characteristics of particles. The parameterization proposed here may be regarded as a simplified version of the Phillips et al (31) scheme that can be readily and immediately applied in many existing cloud and climate models, and in which the number concentrations of particles larger than 0.5-μm diameter are proxies for aerosol surface areas. Although variations in IN with particle composition are neglected in our scheme, the simpler approach captures most of the variability in IN that is large enough to affect the formation and phase of clouds at temperatures down to −35°C.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of aerosols in this region originate from biomass burning in the Amazon region (14). The IN potential of these aerosols has been observed in many field experiments (15,(16)(17)(18)(19) example, reported that the reduction in the size of cloud droplets and the delay in the onset of precipitation within smoky warm clouds in the Amazon region allow more aerosols and moisture to reach higher altitudes by means of updrafts. This may also be enhanced by the high terrain of the Andes where the very small SCF values appear.…”
Section: Observed Supercooled Clouds and The Relations With Tempera-mentioning
confidence: 97%
“…2. Primary attribution grids for ice crystals at 232 hPa from the DEF-C simulation using the heterogeneous ice nucleation spectra of (A) Phillips et al (20), (B) Phillips et al (21), and (C) Barahona and Nenes (22). Ice crystal formation is assumed to occur at all model states.…”
Section: Attribution Gridsmentioning
confidence: 99%